Por que mulheres se importam com consentimento em seus livros de romance? - Alves, Evelisie (Universidade Federal de São Carlos, 2025)
This monograph analyzes how consent is discursively constructed in romance novels written by women (2006–2023), in the light of the concepts of ideological sign and dialogic relations (Bakhtin, 2011; Volóchinov, 2017). Based on fifteen works from different subgenres of the romance genre (contemporary, historical, fantasy), we carried out a qualitative analysis of excerpts in which consent is verbalized, negotiated or revoked. The research objectives were: (i) to describe the linguistic markers of consent (direct questions, modalizers, pauses, gestures); (ii) to examine the power relations implied in the scenes (agency, care, asymmetries); (iii) to interpret consent as an ideological sign in dispute between autonomy and hierarchy. The study adopts a qualitative, inductive, exploratory and explanatory approach, combining discourse analysis with the interpretative reading of selected passages, in dialogue with Bakhtinian theory. The results indicate a predominance of processual consent (asking–answering–confirming–revoking), with strong emphasis on comfort and safety, as well as tensions in which checking coexists with paternalistic traits (“trust me?”, for example). We conclude that contemporary popular romance functions as a discursive laboratory: it normalizes practices of negotiation and revocability of desire, while refracting the gender ideologies of its time.
Why do women care about consent in their romance novels?
Keywords: Consentimento; Dialogismo; Signo ideológico; Romances contemporâneos; Autoria feminina; LINGUISTICA, LETRAS E ARTES; 4. Educação de Qualidade; 5. Igualdade de Gênero; 10. Redução das Desigualdades